On Displacement and Music: Embodiments of Contemporary Nubian Music in the Nubian Resettlements - Kaddal, Fayrouz (AUC Knowledge Fountain, 2021)
Between 1961-1964, an estimated number of 113’000 Nubians, who were living south of the site of the Aswan High Dam, the area now beneath Lake Nasser, and Wadi Halfa, north of Sudan, were displaced to an area near Kom Ombo, 20 kilometres away from the Nile and 50 kilometres north of Aswan. This major project of resettlement occurred for the construction of the Aswan High Dam, Nasser’s signature mega-project. The 1961-1964 displacement was the culmination of earlier waves of relocation that Nubians witnessed during their recent history. In 1902 the British constructed the Aswan (lower) Dam by the first cataract in order to maximise the benefit from regulating the water of the Nile. This smaller dam and its subsequent heightening in 1912 and again in 1933 resulted in population relocation which fed into a pattern of Nubian emigration towards the cities of Cairo and Alexandria. Such pattern was already a feature of Nubian social life during the 19th century, and was mainly motivated by seeking employment opportunities. In this thesis, I study the relationship between displacement and music in the Nubian context. I focus on Nubian musical practices in the displaced village of New Toushka, Kom Ombo, where my ancestors were relocated in 1964. I also examine Nubian music available immediately prior to the 1964 displacement, as well as popular Nubian music. There are limited recordings, and even less scholarly studies available on Nubian music, prior to the 1964 displacement: despite the anthropological and archeological studies by various researchers and institutions right before and during the displacement, music was not a significant consideration throughout this period. However, Countess Anna Hohenwart-Gerlachstein made numerous audio recordings in various villages of music and songs during her two journeys to Nubia in 1962 & 1963. The recordings, which are held at the Phonogram archive of the Austrian Academy of Sciences in Vienna, are among the earliest field recordings of Nubian music to be made, and cover the period immediately before the displacement, including recordings from the village of Toushka, the primary site of my field research. By analysing Nubian music archived, joining music practitioners from both villages and engaging as a musician in their various events and locations, whether in weddings, concerts, or production studios, I ask what is the relationship between displacement, memory and music in the context of Nubian displacement. How years after the Nubian resettlement project, music continues to be an “archive” and a living historical memory of the displacement? What role does music play in shaping the younger generations’ understanding of “Nubian-ness”? How do spaces and temporalities influence people’s understanding of ‘Nubianness’ and musicians’ practice of “Nubian music”? And finally, how do the socio-economic and political contexts, as well as the development of the music globally, contribute in shaping the different constructs of Nubian culture, musical practices and identities.